2018
DOI: 10.3390/su10103525
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Environmental Efficiency of the EU Countries Using Two-Step DEA Approach

Abstract: The article discusses the environmental efficiency of the countries of the European Union and its main objective is to verify models that could be used to explain changes in efficiency in selected countries and to add to the contributions of other authors. Two-step Data Envelopment Analysis (DEA) has been used, which is a suitable method for verifying the statistical significance of environmental variables. Two DEA models—CCR and BCC—were used and efficiencies have undergone a double-bootstrap procedure. As in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…We designed this model based on the results of the analysis but based on EU objectives and a thorough knowledge of waste management in the Slovak Republic. Slovakia is one of the weaker countries in terms of environmental efficiency, along with neighboring countries that are also EU Member States [16,40,41]. The implementation of such a proposed conceptual model is demanding in terms of personnel and financial resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We designed this model based on the results of the analysis but based on EU objectives and a thorough knowledge of waste management in the Slovak Republic. Slovakia is one of the weaker countries in terms of environmental efficiency, along with neighboring countries that are also EU Member States [16,40,41]. The implementation of such a proposed conceptual model is demanding in terms of personnel and financial resources.…”
Section: Discussionmentioning
confidence: 99%
“…In the same year, an Environmental Protection Agency was established in the United States, whose guidelines had a huge impact on the development of theories and practices in global environmental policies. It is the documents that have started to solve the problems of our planet comprehensively, globally, and there is an initial desire for efficient resource management [16]. In the course of history, individual approaches have changed, many authors have argued that there is no sustainable development, that it is only abstraction, others have brought solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al [31] combined the DEA and fuzzy integral assessment methods to analyze eight typical western regions in China; the results can help local governments take corresponding measures to improve their environmental performance level. Lacko and Hajduova [32] used a two-stage DEA approach to assess environmental efficiency of the EU countries, and found that the climate change and socio-economic factors are the most relevant and significant. Moutinho et al [33] utilize DEA and Malmquist productivity index to evaluate the eco-efficiencies of German and French cities, and found that high GDP over CO 2 emissions does not imply high eco-efficiency scores.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The selection of the DEA model based on RTS can be assessed according to three methods, as specified Seiford and Zhu (1999), i.e., CCR RTS method, BCC RTS method, and scale efficiency index method. For evaluation of territorial efficiency, DEA in the form of the CRS model is often used, e.g., Lacko and Hajduová (2018), Makridou et al (2014), Otsuka (2014), or Malhotra and Malhotra (2006).…”
Section: Dea-based Malmquist Productivity Indexmentioning
confidence: 99%